Educação corporativa : uma análise sobre sua contribuição no desenvolvimento de competências no trabalho em uma empresa de mineração - Nascimento, Patrícia Oliveira (2014)
This paper aims to describe a development program offered by the Corporate University of mining company with operations in Vitória/ES, and understand the possible relationship of this program to the development of professional competencies expected by the